Small cell lung cancer: circulating tumor cell lines and expression of mediators of angiogenesis and coagulation - Barbara Rath; Adelina Plangger; Lukas Klameth; Maximilian Hochmair; Ernst Ulsperger; Bram Boeckx; Christoph Neumayer; Gerhard Hamilton (Open Exploration Publishing Inc., 2023)
Aim: Coagulation is frequently activated in cancer patients and has been correlated with an unfavorable prognosis. To evaluate whether a putative release of tissue factor (TF) by circulating tumor cells (CTCs) represents a target to impair the dissemination of small cell lung cancer (SCLC), the expression of relevant proteins in a panel of permanent SCLC and SCLC CTC cell lines that have been established at the Medical University of Vienna. Methods: Five CTC and SCLC lines were analyzed using a TF enzyme-linked immunosorbent assay (ELISA) tests, RNA sequencing, and western blot arrays covering 55 angiogenic mediators. Furthermore, the influence of topotecan and epirubicin as well as hypoxia-like conditions on the expression of these mediators was investigated. Results: The results demonstrate that the SCLC CTC cell lines express no significant amounts of active TF but thrombospondin-1 (TSP-1), urokinase-type plasminogen activator receptor (uPAR), vascular endothelial-derived growth factor (VEGF) and angiopoietin-2 in two cases. The major difference between the SCLC and SCLC CTC cell lines found was the loss of the expression of angiogenin in the blood-derived CTC lines. Topotecan and epirubicin decreased the expression of VEGF, whereas hypoxia-like conditions upregulated VEGF. Conclusions: Active TF capable of triggering coagulation seems not to be expressed in SCLC CTC cell lines in significant levels and, thus, CTC-derived TF seems dispensable for dissemination. Nevertheless, all CTC lines form large spheroids, termed tumorospheres, which may become trapped in clots of the microvasculature and extravasate in this supportive microenvironment. The contribution of clotting to the protection and dissemination of CTCs in SCLC may be different from other solid tumors such as breast cancer.